2013
DOI: 10.1158/1535-7163.mct-13-0010
|View full text |Cite
|
Sign up to set email alerts
|

PARP1 Is Overexpressed in Nasopharyngeal Carcinoma and Its Inhibition Enhances Radiotherapy

Abstract: Nasopharyngeal carcinoma is a rare but highly invasive cancer. As options of agents for effective combination chemoradiotherapy for advanced nasopharyngeal carcinoma are limited, novel therapeutic approaches are desperately needed. The ubiquitin ligase CHFR is known to target PARP1 for degradation and is epigenetically inactivated in nasopharyngeal carcinoma. We present evidence that PARP1 protein is indeed overexpressed in nasopharyngeal carcinoma cells in comparison with immortalized normal nasopharyngeal ep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 34 publications
3
61
0
Order By: Relevance
“…Since there are already PARP inhibitors in the clinical use of solid malignancies (15), it might offer an interesting possibility to control the development of radioresistance. In favor of this, a recent study also demonstrated that inhibiting PARP1 enhances radiotherapy responses in nasopharyngeal carcinoma (16). If similar results could be found in lymphomas and the results presented here are confirmed in independent studies, the role of PARP inhibitors could be tested in the KDM4D-overexpressing subpopulations of Hodgkin lymphoma.…”
Section: Discussionsupporting
confidence: 79%
“…Since there are already PARP inhibitors in the clinical use of solid malignancies (15), it might offer an interesting possibility to control the development of radioresistance. In favor of this, a recent study also demonstrated that inhibiting PARP1 enhances radiotherapy responses in nasopharyngeal carcinoma (16). If similar results could be found in lymphomas and the results presented here are confirmed in independent studies, the role of PARP inhibitors could be tested in the KDM4D-overexpressing subpopulations of Hodgkin lymphoma.…”
Section: Discussionsupporting
confidence: 79%
“…PARP1 played an important role in DNA damage repair, [15][16][17], which made PARP1 a valuable therapeutic target in the research of disease drug. Recently, it was found that PARP1 presented high expression in a series of cancers, which provided a high-value target for the study of tumor detection, stage and biological characteristics [18][19][20][21][22][23]. The overexpression of PARP1 results from much DNA damage in cancer cells with unstable genes, instead of the induction of the activated specific carcinogenic pathway [24].…”
Section: Discussionmentioning
confidence: 99%
“…37 Because radiation therapy itself exploits differences in repair capacity between tissues, that the combination of radiation with PARP inhibitors is effective against cancers that have BRCA, MRE11, and other DNA-repair-protein mutations is no surprise. [39][40][41][42][43][44] However, PARP-1 is also activated by oxidative and nitrative stress, and is a known cofactor for nuclear factor κB (NF-κB)-driven inflammatory gene expression; 45 radiosensitization by PARP inhibitors might also be the result of inhibition of this crucial survival pathway ( Figure 2). 46 Not surprisingly, many clinical trials of PARP inhibitors in combination with radiation therapy are ongoing.…”
Section: Targeting Dna Damage and Repairmentioning
confidence: 99%